2016
DOI: 10.14687/jhs.v13i3.3801
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of university students on gender roles<p>Üniversite öğrencilerinin toplumsal cinsiyet rollerine ilişkin bakış açıları

Abstract: Objective: This study was performed as a descriptive study in order to determine the perspectives of university students on gender roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 1 publication
(5 reference statements)
2
1
0
7
Order By: Relevance
“…In our study, the gender-role scores of female students were not significantly affected by income level. 21 reported that there were no significant differences between socioeconomic level and gender-role attitudes in a similar manner as our study. However, when the literature was examined, there were also studies indicating that socioeconomic status positively affects gender perception.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the gender-role scores of female students were not significantly affected by income level. 21 reported that there were no significant differences between socioeconomic level and gender-role attitudes in a similar manner as our study. However, when the literature was examined, there were also studies indicating that socioeconomic status positively affects gender perception.…”
Section: Discussionsupporting
confidence: 88%
“…Students who have a nuclear family type have higher mean female gender roles and traditional gender roles sub-dimension scores from the GRAS and its sub-dimensions than those with an extended family. Similarly to the findings of the study Dinç and Çalışkan (2016), Başçı and Giray (2016), Seyitoğlu-Çelik, Güneş and Gökçe (2016) indicated that students from nuclear families exhibited a more egalitarian approach than other students. Unlike Ergin, Bekar and Acar-Aydemir (2019) stated that those with divorced parents had more egalitarian attitudes.…”
supporting
confidence: 59%
“…Türkiye'de, farklı bölümlerde eğitim alan üniversite öğrencileri ve öğretmen adayları ile toplumsal cinsiyet konusunda yapılmış çalışmalar arasında toplumsal cinsiyet rolleri ve eşitliğine ilişkin algı, tutum ve deneyimlerini belirleme (Adana vd., 2011;Arıcı, 2011;Dinç ve Çalışkan, 2016;Esen, Siyez, Soylu ve Demirgürz, 2017;Seçgin ve Tural, 2011;Sis Çelik, Pasinlioğlu, Tan ve Koyuncu, 2013;Vefikuluçay, Zeyneloğlu, Eroğlu ve Taşkın, 2007), toplumsal cinsiyetle ilgili farkındalık yaratma (Erden, 2009;Esen, 2013b;Özcan, 2012), özyeterlik ve toplumsal cinsiyet algısı ilişkisini (Özpulat, 2016) belirleme amacıyla yapılmış çalışmalar yer almaktadır. Esen (2013a) üniversite öğrencileriyle yaptığı araştırmasında öğrencilerin eğitim hayatlarında karşılaştıkları cinsiyet ayrımcılığını incelemiştir.…”
Section: Türk Eğitim Sisteminde Toplumsal Cinsiyet Eşitliğiunclassified